The Role of Vitamin E in Peyronie’s Disease - Ricky Suritno (Cermin Dunia Kedokteran, 2018)
Peyronie’s disease (PD) is a disorder of tunica albuginea of corpus cavernosum characterized by the formation of plaque and fibrosis. Oral therapy is a promising non-operative modality. Vitamin E as a well-known antioxidant, is the oldest substance used since 1948 to treat Peyronie's disease. The mechanism is to inhibit the production of inflammatory reactive oxygen species (ROS). There is still controversy on the effectiveness of vitamin E in Peyronie’s disease management.Penyakit Peyronie merupakan gangguan jaringan ikat tunica albuginea corpus cavernosum yang mempunyai karakteristik plak dan fibrosis. Terapi oral merupakan modalitas terapi non operatif yang menjanjikan. Vitamin E sebagai antioksidan yang sudah banyak dikenal, merupakan terapi tertua sejak tahun 1948. Mekanismenya adalah untuk menghambat produksi reactive oxygen species (ROS). Sampai saat ini efektivitas vitamin E untuk penyakit Peyronie masih kontroversial.